Thrombosis, Atherosclerosis and Atherothrombosis New Insights and Experimental Protocols - Bozic-Mijovski, Mojca (IntechOpen, 2015)
Atherosclerosis and thrombosis are a major source of morbidity and mortality in the modern world. Great advances have been made in the past decades in our understanding of the pathophysiology of atherosclerosis and thrombus formation. This book offers a broad, contemporary review of atherosclerotic processes, with the latest research advances on inflammation and hypercoagulability that lead to thrombosis. In addition, experimental protocols are included, by which atherosclerotic processes are studied, providing the reader with the information necessary to understand the complexity of the disease process and the current experimental methodology in finding new answers that would help in the diagnosis, prevention and treatment of atherosclerotic disease.